2017
DOI: 10.7196/sajog.1124
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes in pregnant women presenting with preterm premature rupture of membranes at a regional hospital in KwaZulu- Natal Province, South Africa

Abstract: Background. Worldwide, the incidence of preterm premature rupture of membranes (PPROM) is between 1% and 4% of all pregnancies. Objectives. The primary objectives of this study were to describe and compare the perinatal outcomes of HIV-positive and HIV-negative women presenting with PPROM to a regional hospital in KwaZulu-Natal. Methods. This was a retrospective analytical cross-sectional study which reviewed files of pregnant women presenting with premature rupture of membranes at gestation between 28 and 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
5
0
1
Order By: Relevance
“…Although studies by Gahwagi et al [13] in Libya and Boskabadi and Zakerihamidi [25] in Iran showed no significant association between gestational age with PROM, our study found that pregnant women of 37 weeks and more were less likely to experience PROM compared to early gestation women of less than 34 weeks (aOR = 0:3, 95% CI: 0.14-0.71, p = 0:01). Similar observations were made by Shadma and Aymen [4] in India, Abouseif et al [19] in Egypt, and Msomi et al [26] in South Africa where majority of the women with PROM were below 34 weeks of gestation. This is probably due to gestational age-related differences regarding fetal presentation, fetal position, and fetal lie, as well as maternal physiology.…”
Section: Discussion Of the Findingssupporting
confidence: 87%
“…Although studies by Gahwagi et al [13] in Libya and Boskabadi and Zakerihamidi [25] in Iran showed no significant association between gestational age with PROM, our study found that pregnant women of 37 weeks and more were less likely to experience PROM compared to early gestation women of less than 34 weeks (aOR = 0:3, 95% CI: 0.14-0.71, p = 0:01). Similar observations were made by Shadma and Aymen [4] in India, Abouseif et al [19] in Egypt, and Msomi et al [26] in South Africa where majority of the women with PROM were below 34 weeks of gestation. This is probably due to gestational age-related differences regarding fetal presentation, fetal position, and fetal lie, as well as maternal physiology.…”
Section: Discussion Of the Findingssupporting
confidence: 87%
“…Furthermore, the proportion of women on cART or with lower CD4 count or higher viral load was equally distributed among women with PPROM or without PPROM. The overall high HIV seroprevalence in our cohort is consistent with that reported in another PPROM study in the KZN region and the most recent national antenatal HIV survey [22,27]. Unfortunately, the other KZN study lacked a control group of preterm deliveries without PPROM.…”
Section: Discussionsupporting
confidence: 89%
“…Inconsistent with our high cesarean rate, the other KZN PPROM study reported a higher vaginal delivery rate among women with PPROM but did not compare this with other preterm deliveries [22]. Nonetheless, similar to our findings, there was no evidence of worse pregnancy and newborn outcomes among HIV-infected women with PPROM when compared to their HIV-uninfected counterparts [22]. As in our study, most HIV-infected women in the study by Msomi et al were also on cART prior to delivery [22].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations